The impact of training on productivity and wages: Evidence from British panel data - Lorraine Dearden; Howard Reed; John Van Reenen (Institute for Fiscal Studies (IFS), 2005)
It is standard in the literature on training to use wages as a sufficient statistic for productivity. This paper examines the effects of work-related training on direct measures of productivity. Using a new panel of British industries 1983-1996 and a variety of estimation techniques we find that work-related training is associated with significantly higher productivity. A one percentage point increase in training is associated with an increase in value added per hour of about 0.6% and an increase in hourly wages of about 0.3%. We also show evidence using individual level datasets that is suggestive of training externalities.
Keywords: J31; C23; D24; 330; Productivity; training; wages; panel data; Berufsbildung; Arbeitsproduktivität; Lohn; Großbritannien